Teachers’ views on the effect of STEM education on the labor market - Akcan, Ahmet Tayfur; Yıldırım, Bekir; Karataş, Ali Rauf; Yılmaz, Mustafa (Frontiers in Psychology, 2023)
This paper explores teachers' views on the impact of STEM education on the labor market. This study focused on teachers' views to investigate STEM education and the labor market and the relationship between the two. The sample consisted of 32 teachers from different branches. Participants were recruited using purposive convenience sampling. This paper adopted a qualitative case study research design. Qualitative data were collected using a semi-structured interview form. The qualitative data were analyzed using inductive content and descriptive analysis. Participants stated that STEM education offered new fields of work, promoted entrepreneurship, and increased job opportunities. They also noted that STEM education helped reduce social costs. They emphasized that STEM education made participants happy, prevented brain drain, and reduced social problems. On the other hand, they also noted that STEM education could lead to technological unemployment. The descriptive analyses showed that STEM education had a positive impact on employment, a reduction in social costs, and a positive impact on underemployment. In light of the results, we made recommendations for future research.